Assessing the Performance of CareStart Malaria Pf/Pv Combo Test Against Thick Blood Film in the Diagnosis of Malaria in Northwest Ethiopia - Hailu, Tadesse (The American Society of Tropical Medicine and Hygiene, 2014)
Bivalent rapid diagnostic tests are promising diagnostic tools for Plasmodium falciparum and P. vivax. Their diagnostic performance was evaluated against thick blood smear to assist national malaria control programs. A cross-sectional study was conducted to evaluate the performance of CareStart against thick blood smears among 398 acute febrile patients visiting the Felegeselam Health Center in December of 2011. Thick blood smears were examined under 100× objectives to diagnose Plasmodium species. Similarly, CareStart Malaria Pf/Pv Combo Test was performed as per the manufacturer's instruction. The ability of CareStart Malaria Pf/Pv Combo Test to diagnose Plasmodium malaria was very good, with 99.8% (95% confidence interval = 97.7–100%) sensitivity and 97.7% (95% confidence interval = 94.6–99.1%) specificity. The sensitivity and specificity of the CareStart Test is comparable with the thick blood smear in diagnosing malaria. Hence, it is preferable to use the CareStart Malaria Pf/Pv Combo Test instead of microscopy in areas where microscopic diagnosis is limited.